Experimental Study on the Enhancement of Particle Removal Efficiency in Spray Tower Scrubber Using Electrospray - Hyeok-Gyu Kim; Hong-Jik Kim; Myong-Hwa Lee; Jong-Ho Kim (Asian Journal of Atmospheric Environment, 2014)
There have been a lot of efforts to keep permissible emission standards and to reduce the amount of emitted air pollutants. There are several air pollution control equipments, however, wet scrubber is used to remove particulate matters and gaseous pollutants simultaneously, even if it has low collection efficiency in the particle size less than 5.0 μm. To overcome this problem, we introduced a spray tower scrubber with an electrospray system which a high voltage was indirectly applied. We found that collection efficiency of fine particles in the electrospray system was improved by increasing electrical field strength and the ratio of liquid-gas flow rate (from 41% to 84% for 0.3 μm particles). In addition, a number of small droplets generated from an electrospray system led high collection efficiency, resulting from electrostatic attraction between droplets and particles and higher collision frequency. Therefore, we can conclude that the introduction of an electrospray system is quite effective to increase the particle removal efficiency of a spray tower scrubber.